Socio-demographic and health profile of schedule tribes of Velugodu, Andhra Pradesh, India - S. Dondapati, Sujith Kumar; Karimaddela, Keerthinmayee (International Journal Of Community Medicine And Public Health, 2016)
Background: Scheduled Tribes live in unique physical, socio-economic and cultural environment, isolated from general population. The tribal population is at a higher risk of under-nutrition, because of the socio-cultural, socio-economic and environmental factors influencing the food intake and health seeking behavior. Inadequate health care facilities, illiteracy and socio-economic disadvantage among tribal populations perpetuate the vicious cycle of under nutrition. Methods: A pre-tested questionnaire containing information on household socio-economic and demographic particulars like type of family, religion, caste, age, gender, income, literacy, occupation was administered by paying house to house visits. A detailed clinical examination for assessment of nutritional status, history, signs and symptoms of current illness was carried. Results: 92% of the families are nuclear followed by joint, 3 generation and extended families. The average size of the family is 3.64. 97% practice Hinduism. The sex ratio is 987 females for 1000 males. 72% of the populations are illiterate. 40% of the populations earn their livelihood by collecting NTFP. 59% of under-fives, 30% of school going and adolescents and 60% of adults are under nourished. Conclusions: Socio demographic profile is similar to other Schedule Tribes and chenchu populations in India and other parts of Andhra Pradesh. Under nutrition is high among under-fives and adults. Scabies, anaemia and eruptive fevers are the common health problems after malnutrition.